Sujeito e sentidos sobre o feminino em A hora da estrela de Clarice Lispector. - Arruda, Maria de Lourdes Alves (2019)
The present work analyzes the working of senses on the feminine in the work The hour of the star, by Clarice Lispector. We anchor our work to the perspective of Discourse Analysis of French matrix and with it entering the interface language/literature, we put as main scope the analysis of the corpus formed by cuts of the text, trying to cross the paths of the crystallization of the dominant senses, at the time of writing of the work, on the feminine image, in the confrontation of the characters‘ profiles. In other words, we investigate the socio-historical conditions of textual production of the work, analyzing and identifying brands of power relations present in the text and their relations with socio-historical-ideological conditions that cross the formulation of meanings about being a woman. The object of analysis of this work sought to approximate to the paths of a qualitative research and aims the comprehension of discursive constructions that form the feminine, in the search of its constitutive elements through the discourse at a certain time in history. In the first chapter, we consider the work, the literature and its articulation with the AD, as well we approach the authorship. In the second chapter, we consider the dialogue of these two disciplines, we approach the discursive memory and the silence, then we start with the analysis of the functioning of the senses in the third chapter. Our analysis concluded that the senses underlying to the formation of the feminine in the 1970s express the crystallization of senses derived from earlier times, which basis is rooted in the power relations subtly disseminated by the ideology of masculine superiority over the feminine. We also conclude that there is an express mobility in these senses that mark the way of the women in search of their autonomy, in a course where operate the divergence and contradiction that establish the dialogue with the movement, constructing the multiplicity of senses on the being woman.